Detecting the “Wish Not to Live”: Rasch Validation of the D-PSI Scale for Technology-Enabled Suicide Prevention in Higher Education - Haryadi, Rudi; Ramli, M; Hidayah, Nur; Muslihati, Muslihati; Talib, Mansor bin Abu (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study aims to develop and psychometrically validate a culturally grounded Distinctive Passive Suicidal Ideation Scale and to examine its potential contribution to early suicide prevention within technology-supported higher education environments. Methodology: This quantitative cross-sectional study employed a self-developed Distinctive Passive Suicidal Ideation Scale administered through an online survey using Google Forms. Data were collected from 833 Indonesian respondents. Psychometric validation was conducted using Item Response Theory with Rasch modeling. Item difficulty, person reliability, item fit statistics (infit and outfit MNSQ), rating scale functioning, and person–item targeting were analyzed using Jamovi version 2.7.6. Main Findings: The Scale demonstrated strong psychometric performance. The Rasch analysis indicated high person reliability (0.917) and acceptable item fit statistics, confirming the internal consistency of the scale. Item difficulty estimates clustered within low to moderate levels, suggesting that the instrument is sensitive to early manifestations of passive suicidal ideation. Rating scale thresholds were ordered, and person–item targeting indicated appropriate alignment between item difficulty and respondent ability levels. Novelty/Originality of this study: This study introduces a Rasch-validated instrument designed to measure passive suicidal ideation as the cognitive state described as the “wish not to live.” By operationalizing this early stage of suicidality, the D-PSI Scale provides a psychometric foundation for integrating psychological screening indicators into digital counseling platforms, learning analytics, and other technology-enabled student support systems aimed at strengthening suicide prevention efforts in higher education.